IMPLEMENTASI KEBIJAKAN PENGEMBANGAN SUMBER DAYA MANUSIA PADA DINAS KESEHATAN KABUPATEN YAHUKIMO - Pendius Wanimbo; Nur Aedah; Hiskia C.M. Sapioper (JURNAL KEBIJAKAN PUBLIK, 2020)
Human Resources (HR) with important quality are optimized to support the implementation of accelerated development. This research was conducted at the Yahukimo District Health Office, with a focus on the implementation of policies on the development of the quality of Human Resources and the supporting and inhibiting factors for HR development. This research paradigm is qualitative with descriptive research type. The technique of determining informants uses the technique snowball. Research informants. Primary data collection is done by interview (interview), observation non participant. Secondary data were obtained from manuals, reports, newspaper clippings, and literature relating to research problems, such as books and journals. Methods of data analysis through stages of reduction, data presentation and taking conclusions. The results showed that the implementation of the human resources development policy of the Yahukimo Health Office with Edward III mode showed that the communication and policy guidelines for the HR development of the Yahukimo District Health Office had gone well. The relationship is built from the line hierarchy of the department head to the related fields. The head of the department entrusts the head of the Technical SDK to carry out their duties and functions according to the guidelines and instructions. The Department of Health's resources are severely short on the number of health workers in the field. The number of Puskesmas in Yahukimo Regency with a total of 33 does not match the composition of the existing health personnel. The disposition or tendency of employees at the Health Office in implementing HR development policies is carried out with regular coordination between the head of the department and subordinates. This cross-coordination can be carried out not only on a top-down but also bottom-up basis according to the hierarchical structural coordination line. The bureaucratic structure for implementing HR development policies has SOPs that include an Integrated Recording and Reporting System, Integrated Technical Guidance SOPs and Civil Servant Performance Target SOPs. Support for Policy Implementation is the absorption of the Special Autonomy Fund of two billion Rupiah which is specifically allocated for employee education. Meanwhile, the obstacles cover three things, namely the lack of technical guidance and training, minimal budgetary resources, and inadequate access to transportation.